Efektivitas Kebijakan Pembangunan Underpass Simpang Kentungan dalam Mengurai Kemacetan di Daerah Istimewa Yogyakarta - Muhammad Fahmi Idris; Rahmawati Husein (Journal of Social and Policy Issues, 2022)
This research aims to analyze government policies on the effectiveness of government programs in overcoming congestion problems by building underpasses in Simpang Kentungan, Sleman Regency. Indicators of this research are program understanding, on target, on time, achievement of goals, real change before and after the underpass. The research is located in Simpang Kentungan, Depok District, Sleman Regency, using a qualitative approach, where the data is used in the form of primary and secondary data. Research data is obtained from interviews, observations, and documentation on similar studies. Based on the results of the study showed that the government's policy in overcoming congestion in Simpang Kentungan are effective, although at the time of operation of the underpass there were still some problems such as damage to the grill or drainage and water pumps that did not work when the rains were large, thus causing puddles on the underpass.